28.9k views
2 votes
Solve the equation

{5}^(n + 1) - {5}^(n) + {5}^(n - 1) = 105


User Alchi
by
5.0k points

2 Answers

1 vote
n=2 is the correct answer yes
User NGoline
by
5.6k points
3 votes

Answer:

n=2

Explanation:

Hello, please consider the following.


{5}^(n + 1) - {5}^(n) + {5}^(n - 1) = 105\\\\5^(n-1)(5^2-5+1)=5^(n-1)(25-5+1)=21*5^(n-1)=105\\\\5^(n-1)=(105)/(21)=5=5^1\\\\\text{It means that}\\\\n-1=1 <=> n=2

Let me know if you need more details.

Thank you

User Shurmajee
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.